VIEWS OF ACCOUNTING STUDENTS ON CAREER SELECTION AS EDUCATOR ACCOUNTANTS - Risma Sofi Bintari (Nindikayla Institute, 2023)
This research aims to identify the perception of accounting students towards choosing career in which as accountant lecturer. In this research, the student's perception is measured by financial reward, professional training, social values, work environment, and consideration of labor market need. The object of these research was accouting students who programmed thesis in odd semester 2015/2016. 30 students were participating as respondent from four university in Surabaya—data analysis of this research using analysis descriptive from observation, questionnaire, and interview with accounting students. The result shows that from 30 students who become respondent, there were only 7 students who choosen the accountant lecturer; the most attractive factor is work environmental. While the most desirable factor in consideration of labor market need